2018
DOI: 10.1186/s13756-018-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-contamination during doffing of personal protective equipment by healthcare workers to prevent Ebola transmission

Abstract: BackgroundHealthcare workers (HCWs) use personal protective equipment (PPE) in Ebola virus disease (EVD) situations. However, preventing the contamination of HCWs and the environment during PPE removal crucially requires improved strategies. This study aimed to compare the efficacy of three PPE ensembles, namely, Hospital Authority (HA) Standard Ebola PPE set (PPE1), Dupont Tyvek Model, style 1422A (PPE2), and HA isolation gown for routine patient care and performing aerosol-generating procedures (PPE3) to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 19 publications
0
73
0
7
Order By: Relevance
“…All endoscopy staff must receive adequate education and enhanced training relating to the use of PPE to minimize protocol deviations as self‐contamination during doffing is frequently encountered 58 . Many resources are readily available from various institutions and the web.…”
Section: Methodsmentioning
confidence: 99%
“…All endoscopy staff must receive adequate education and enhanced training relating to the use of PPE to minimize protocol deviations as self‐contamination during doffing is frequently encountered 58 . Many resources are readily available from various institutions and the web.…”
Section: Methodsmentioning
confidence: 99%
“…No studies exist that directly compare the different respirators' abilities to prevent transmission of viral illness in the health care setting. Such studies would need to incorporate doffing and reprocessing procedures in the experimental design, since there is high risk of transmission if doffing is performed incorrectly, and the risk may be modified by the type of PPE used [71]. .Experimental studies in the occupational health literature have been performed that compare how well different respirators filter aerosols (typically sodium chloride aerosols) in simulated industrial environments.…”
Section: The Risk Of Exposure To Covid-19 When a Patient's Covid-19 Smentioning
confidence: 99%
“…However, at a minimum, otolaryngologists should don a respirator, gown, cap, eye protection, and gloves [17]. Moreover, studies from the Ebola outbreak reported that in some circumstances, up to 79.2% of providers self- contaminated while removing PPE [18]; therefore, careful consideration must be applied to doffing PPE during the COVID-19 pandemic. Even after exercising adequate precautions, it is sensible to recommend that vulnerable demographics limit their exposure to possible COVID-19 infection as much as possible [19].…”
Section: Discussionmentioning
confidence: 99%